Oxidant‐Accelerated Polydopamine Modification Process for the Fast Fabrication of PDA on HMX with Improved Mechanical Stability. Issue 5 (2nd March 2021) - Duan, Shuyi; Wang, Dehai; Jiang, Quanping; Xiao, Chun; Liu, Huihui; Guo, Ya; Li, Shangbin; Zhu, Qing
Abstract: Polydopamine surface coating shows the capability to improve the adhesive properties as well as mechanical stabilities of energetic materials, which is highly desired for the development of insensitive munitions. However, the slow polymerization process of dopamine makes the coating process time‐consuming and uneconomic. Herein, an oxidant‐accelerated strategy was demonstrated to obtain fast polymerization kinetics of dopamine for the surface modification of HMX crystals. Upon the addition of oxidant, PDA was able to form surface layer of HMX particles within 5 min without changing the shape and polymorph of HMX crystals. The PDA coating showed the ability to improve the wettability of HMX, contributing to its abundant active groups. Moreover, the mechanical stability of PDA on HMX (HMX@PDA) samples was improved accompany with the increasing coating time, and the friction explosion probability and drop height of 300 s treated sample were 40 % and 64 cm, respectively. The detonation velocity was also measured, which showed that the effect of PDA coating on the detonation velocity of HMX was not significant. More importantly, our protocol showed the capability to fabricate HMX@PDA with different particle sizes on a large scale, satisfying the application demands of insensitive high explosives. Abstract :